Substitutions in football - what coaches think and what coaches do - Wittkugel, J.; Memmert, D.; Wunderlich, F. (Journal of Sports Sciences, 2022)
Substitutions are probably the most important opportunity for football coaches to actively influence a match in progress. The present article presents two studies investigating substitutions in football from two different methodological perspectives: Study I, a survey reporting the opinions of 73 licensed coaches, and Study II, data-based analysis of a total of 41,301 substitutions from 7,230 matches in seasons 2014/15 to 2018/19 of the top four European football leagues. The coaches stated to prefer offensive substitutions over defensive substitutions and additionally indicated that changing the current score was more likely to be a reason for substitution than keeping the score. The analysis of the data revealed that not offensive, but neutral substitutions, where the player is replaced by a player of the same playing position, were most frequent. However, offensive players participated significantly more frequently in substitutions. In addition, a high level of score dependence was found, as more than half of the defensive substitutions were made while winning and more than half of the offensive substitutions were made while losing. The present study sheds light on the substitution behaviour of coaches in football and intends to stimulate discussion on the optimal timing and the type of substitutions.